Orienteering for people with intellectual disabilities - Jesús Muñoz Jiménez; Paloma Rodríguez Jiménez; Daniel Collado Mateo; Kiko F. León Guzmán (Federación Extremeña de Balonmano; University of Extremadura, 2016)
The principal aim of the present research is to evaluate the relationship between orientation and cognitive skills in people with intellectual disability throughout some test of a sport Orientation after the making a plan with the subjects where they are going to be trained those capacities. The sample is based on 15 students with intellectual disabilities from a special school "Colegio de Educación Especial PROA" in Cáceres, all of them are aged between 15 and 22. An Orientation test was performed at the beginning of the intervention (pretest), and after several training sessions of the specific sport "Orientacion", the subjects had to perform the same test again (post-test) to quantify the potential performance improvements of the participants The results show that people with intellectual disabilities have an improvement in the performance of an adapted test of orientation after specific training sessions.